Cripto-independent Nodal signaling promotes positioning of the A-P axis in the early mouse embryo - Liguori, Giovanna (2018)
During early mouse development, the TGF beta-related protein Nodal specifies the organizing centers that control the formation of the anterior-posterior (A-P) axis. EGF-CFC proteins are important components of the Nodal signaling pathway, most likely by acting as Nodal coreceptors. However, the extent to which Nodal activity depends on EGF-CFC proteins is still debated. Cripto is the earliest EGF-CFC gene expressed during mouse embryogenesis and is involved in both A-P axis orientation and mesoderm formation. To investigate the relation between Cripto and Nodal in the early mouse embryo, we removed the Nodal antagonist Cerberus 1 (Cer1) and simultaneously Cripto, by generating Cer1;Cripto double mouse mutants. We observed that two thirds of the Cer1,Cripto double mutants are rescued in processes that are severely compromised in Cripto(-/-) embryos, namely A-P axis orientation, anterior mesendoderm and posterior neuroectoderin formation. The observed rescue is strongly reduced in Cer1;Cripto;Nodal triple mutants, suggesting that Nodal can signal extensively in the absence of Cripto, if Cer1 is also inhibited. This signaling activity drives A-P axis positioning. Our results provide evidence for the existence. of Cripto-independent signaling mechanisms, by which Nodal controls axis specification in the early mouse embryo. (C) 2007 Elsevier Inc. All rights reserved.